Short-term fertilizer application alters phenotypic traits of symbiotic nitrogen fixing bacteria - Anna K. Simonsen; Shery Han; Phil Rekret; Christine S. Rentschler; Katy D. Heath; John R. Stinchcombe (PeerJ, 2015)
Fertilizer application is a common anthropogenic alteration to terrestrial systems. Increased nutrient input can impact soil microbial diversity or function directly through altered soil environments, or indirectly through plant-microbe feedbacks, with potentially important effects on ecologically-important plant-associated mutualists. We investigated the impacts of plant fertilizer, containing all common macro and micronutrients on symbiotic nitrogen-fixing bacteria (rhizobia), a group of bacteria that are important for plant productivity and ecosystem function. We collected rhizobia nodule isolates from natural field soil that was treated with slow-release plant fertilizer over a single growing season and compared phenotypic traits related to free-living growth and host partner quality in these isolates to those of rhizobia from unfertilized soils. Through a series of single inoculation assays in controlled glasshouse conditions, we found that isolates from fertilized field soil provided legume hosts with higher mutualistic benefits. Through growth assays on media containing variable plant fertilizer concentrations, we found that plant fertilizer was generally beneficial for rhizobia growth. Rhizobia isolated from fertilized field soil had higher growth rates in the presence of plant fertilizer compared to isolates from unfertilized field soil, indicating that plant fertilizer application favoured rhizobia isolates with higher abilities to utilize fertilizer for free-living growth. We found a positive correlation between growth responses to fertilizer and mutualism benefits among isolates from fertilized field soil, demonstrating that variable plant fertilizer induces context-dependent genetic correlations, potentially changing the evolutionary trajectory of either trait through increased trait dependencies. Our study shows that short-term application is sufficient to alter the composition of rhizobia isolates in the population or community, either directly though changes in the soil chemistry or indirectly through altered host legume feedbacks, and is potentially a strong selective agent acting on natural rhizobia populations.